Pengaruh Media Pembelajaran Interaktif Melalui Game Educaplay Terhadap Peningkatan Pemahaman Tentang Alam Semesta Pada Anak Usia Dini - Ubaidillah Ubaidillah; Nadin Anindya Fadiatur Rohmah; Heppy Purwatih; Zakiyatul Arofah; Alfi Qotrun Nada (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
This research is motivated by the challenges of introducing the abstract concept of the universe to early childhood, where the use of conventional media often results in a lack of student focus. The purpose of this study is to analyze the influence of using interactive learning media through Educaplay games on improving the understanding of the universe in children aged 5-6 years. The research method used is quantitative experimental with a Pre-Experimental design (One Group Pre-test Post-test Design). The research subjects involved 24 students from Group B at TK ‘Aisyiyah 21 Benjeng, Gresik. Data collection techniques were carried out through observation, documentation, and test instruments (pre-test and post-test). Data analysis utilized the Shapiro-Wilk normality test and the Paired Sample T-Test hypothesis test via SPSS software. The results showed an increase in the students' average understanding score from 7.17 in the pre-test to 9.83 in the post-test. The Paired Sample T-Test produced a significance value (2-tailed) of 0.000, which is smaller than the significance level of 0.05 (0.000 < 0.05). This indicates that Ho is rejected and H1 is accepted. Thus, it can be concluded that the use of interactive learning media through Educaplay games significantly influences the improvement of understanding the universe in early childhood. The recommendation of this study is for teachers to integrate interactive digital media into science learning to create a more concrete and enjoyable learning atmosphere